Secret and sacred : an insight on female circumcision - Maendeleo ya wanawake Organization
The video provides a rare insight into the practice of female circumcision/ female genital mutilation (FGM) in Kenya. It is exceptional in its approach because of its sensitivity to the cultural context in which female circumcision prevails.